2021
DOI: 10.1155/2021/6662156
|View full text |Cite
|
Sign up to set email alerts
|

SS‐31 Protects Liver from Ischemia‐Reperfusion Injury via Modulating Macrophage Polarization

Abstract: Ischemia-reperfusion injury (IRI) is a common complication in liver surgeries. It is a focus to discover effective treatments to reduce ischemia-reperfusion injury. Previous studies show that oxidative stress and inflammation response contribute to the liver damage during IRI. SS-31 is an innovated mitochondrial-targeted antioxidant peptide shown to scavenge reactive oxygen species and decrease oxidative stress, but the protective effects of SS-31 against hepatic IRI are not well understood. The aim of our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 56 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…Harvested liver tissues were fixed in 4% formalin and embedded in paraffin blocks. Four-micrometer sections were stained with hematoxylin and eosin (H&E), and liver damage caused by I/R was scored by a pathologist blindly using Suzuki criteria ( 18 ) on a scale from 0–4.…”
Section: Methodsmentioning
confidence: 99%
“…Harvested liver tissues were fixed in 4% formalin and embedded in paraffin blocks. Four-micrometer sections were stained with hematoxylin and eosin (H&E), and liver damage caused by I/R was scored by a pathologist blindly using Suzuki criteria ( 18 ) on a scale from 0–4.…”
Section: Methodsmentioning
confidence: 99%
“…The hepatic warm IRI model was described previously with slight modifications [ 20 ]. In brief, isoflurane in combination with chloral hydrate was used for anesthesia, and the portal vein and arterial blood supply to the left and median liver lobes were blocked using an atraumatic clip.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has demonstrated that SS-31, a mitochondrial-targeted antioxidant peptide, directly decreases ROS production and regulates signal transducer and activator of transcription 1/3 (STAT1/STAT3) signaling in macrophages, causing M2 polarization phenotype. The peptide also decreased the production of proinflammation cytokines, thereby mitigating inflammatory response in the liver [ 81 ].…”
Section: Hepatic Microenvironmentmentioning
confidence: 99%